METHOD OF EVALUATING RADIO-ELECTRONIC EQUIPMENT FAILURE RATES USING REFERENCE DATA - Kuzavkov, Vasyl; Lanko, Anton (Science-based technologies, 2026)
Reliability indicators of radio-electronic equipment (probability of failure-free operation, mean time to failure, failure rate, and availability factor) are typically evaluated through tests or statistical analysis. However, under current conditions, when foreign-made dual-use technical systems with limited input information are used by the armed forces, it’s impossible to properly assess their reliability. This article proposes a method for evaluating one of the reliability indicators of radio-electronic armament samples-the failure rate-based on reference data. The relevance of the work is due to the widespread use of foreign-made technical systems and dual-use samples in the armed forces. Such systems have the following characteristics: they have been stored in warehouses for a long time; they come with limited technical documentation; and there is a lack of technical condition monitoring systems and evaluation methods. Moreover, in most cases, the manufacturer of such systems does not permit repairs to be carried out on the territory of another country. Therefore, the equipment user (maintenance personnel, engineering and technical staff) is forced to find ways to integrate the received equipment into the existing maintenance and repair system and to find ways to assess its reliability. The approach proposed in this work allows for obtaining a value for the failure rate (as one of the reliability indicators), which characterizes the failure-free property of radio-electronic equipment. The method helps to reduce the subjectivity of the reliability assessments obtained and is suitable for foreign-origin equipment supplied without information on manufacturing and testing conditions. The results can be applied in Ukraine’s security and defense sector to integrate radio-electronic equipment into the adopted maintenance and repair system. An example is provided for calculating the failure rate of a hypothetical radio-electronic equipment unit containing various types of radio-electronic components (integrated circuits, resistors, capacitors) based on the MIL-HDBK-217 handbook.